Pharmacokinetics of eribulin mesylate in patients with solid tumours receiving repeated oral rifampicin. (10th January 2013) - Devriese, Lot A.; Witteveen, Petronella (Els) O.; Wanders, Jantien; Law, Kenneth; Edwards, Geoff; Reyderman, Larisa; Copalu, William; Peng, Fuping; Marchetti, Serena; Beijnen, Jos H.; Huitema, Alwin D. R.; Voest, Emile E.; et al.
<x xml:space="preserve">Abstract</x> Aim Eribulin mesylate is a non‐taxane microtubule dynamics inhibitor that was recently approved for treatment of metastatic breast cancer. The aim of this study was to determine the effect of rifampicin, a CYP3A4 inducer, on the plasma pharmacokinetics of eribulin in patients with solid tumours. Methods An open‐label, non‐randomized phase I study was carried out. Patients received intravenous 1.4 mg m−2 eribulin mesylate on days 1 and 15 and oral rifampicin 600 mg on days 9 to 20 of a 28 day cycle. Pharmacokinetic sampling for determination of eribulin plasma concentrations was performed up to 144 h following administration. AUC(0, ∞) and Cmax for eribulin exposure without or with co‐administration of rifampicin were subjected to an analysis of variance (anova) and corresponding 90% confidence intervals (CI) were calculated. Subsequently, patients were allowed to continue eribulin mesylate treatment with 1.4 mg m−2 eribulin mesylate on days 1 and 8 of a 21 day cycle. Also the adverse event profile and anti‐tumour activity were assessed. Results Fourteen patients were included and 11 patients were evaluable for pharmacokinetic analysis. Co‐administration of rifampicin had no effect on single dose exposure to eribulin (geometric least square means ratio: AUC(0, ∞) = 1.10, 90% CI 0.91, 1.34 and Cmax = 0.97, 90% 0.81, 1.17). The most common treatment‐related grade ≥3 adverse events were grade 3 neutropenia (4/14, 29%), leucopenia and fatigue (both 3/14, 21%). Conclusions These results indicate that eribulin mesylate may be safely co‐administered with compounds that are CYP3A4 inducers.